The lives of ordinary people in ancient Israel: where archaeology and the Bible intersect, W.G. Dever : book review - Cronje, S. I. (Journal for semitics, 2014)
For various reasons this book by William Dever is not a history in the usual sense of the word. First, in this work the archaeological data are treated as the primary source, while textual data are only drawn upon once the archaeological data have been exhausted. Second, only the eighth century is treated in this "history". At times Dever does infringe on both the ninth and seventh centuries, but the eighth century remains the focus. According to Dever, the fact that this period is archaeologically well documented favoured the choice of this period as subject matter. Dever basically constructs a parallel history of one era in the history of Israel and Judah to "correct", so to speak, the history we construct according to the Hebrew Bible.